The introvert's way eaudiobook Living a quiet life in a noisy world. - Dembling, Sophia (Your Coach Digital, 2013)
For anyone who loved Susan Cain's Quiet, comes this practical manifesto sharing the joys of introversion... This clever and pithy audiobook challenges introverts to take ownership of their personalities...with quiet strength. Sophia Dembling asserts that the introvert's lifestyle is not "wrong" or lacking, as society or extroverts would have us believe. Through a combination of personal insights and psychology, The Introvert's Way helps and encourages introverts to embrace their nature, to respect traits they may have been ashamed of and reframe them as assets. You're not shy; rather, you appreciate the joys of quiet. You're not antisocial; instead, you enjoy recharging through time alone. You're not unfriendly, but you do find more meaning in one-on-one connections than large gatherings. By honoring what makes them unique, this astute and inspiring audiobook challenges introverts to "own" their introversion, igniting a quiet revolution that will change how they see themselves and how they engage with the world.